Adolescent and Young Adult Patient Engagement and Participation in Survey‐Based Research: A Report From the "Resilience in Adolescents and Young Adults With Cancer" Study. Issue 4 (18th December 2015) - Rosenberg, Abby R.; Bona, Kira; Wharton, Claire M.; Bradford, Miranda; Shaffer, Michele L.; Wolfe, Joanne; Baker, Kevin Scott
Abstract : Conducting patient‐reported outcomes research with adolescents and young adults (AYAs) is difficult due to low participation rates and high attrition. Forty‐seven AYAs with newly diagnosed cancer at two large hospitals were prospectively surveyed at the time of diagnosis and 3–6 and 12–18 months later. A subset participated in 1:1 semistructured interviews. Attrition prompted early study closure at one site. The majority of patients preferred paper–pencil to online surveys. Interview participants were more likely to complete surveys (e.g., 93% vs. 58% completion of 3–6 month surveys, P = 0.02). Engaging patients through qualitative methodologies and using patient‐preferred instruments may optimize future research success.